The blue of the sky: Carlo Scarpa a Palermo - Santo Giunta (Agathón)
Seek the blue of the sky – this is an exhortation from Carlo Scarpa to comprehend being part of a place. In particular, in the re-adaptation of Palazzo Abatellis, he proposed solutions and hypotheses for its re–use in order to redefine an organizational principle upon which to base the existing space and from which rules emerge which, in his treatment, give meaning to the entire physical and visible environment.